2023
DOI: 10.1038/s41598-023-29444-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial helicity response metric to quantify particle size and turbidity of heterogeneous media through circular polarization imaging

Abstract: Backscattered circularly polarized light from turbid media consists of helicity-flipped and helicity-preserved photon sub-populations (i.e., photons of perpendicular and parallel circular handedness). Their intensities and spatial distributions are found to be acutely sensitive to average scatterer size and modestly sensitive to the scattering coefficient (medium turbidity) through an interplay of single and multiple scattering effects. Using a highly sensitive intensified-CCD camera, helicity-based images of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…It is observed that orthogonalization occurs in the backward direction between 135 deg and 225 deg (exact backscattering ±45 deg cone). This angular dependency suggests that linearly orthogonalized photons will exhibit shallower pathways in a polystyrene microsphere suspension (on average), as already shown previously for circularly polarized light 23 . The orthogonalized and preserved (arc-like) pathways are schematized in Fig.…”
Section: Theoretical and Experimental Spatial Analysis Of Polarimetri...supporting
confidence: 70%
See 4 more Smart Citations
“…It is observed that orthogonalization occurs in the backward direction between 135 deg and 225 deg (exact backscattering ±45 deg cone). This angular dependency suggests that linearly orthogonalized photons will exhibit shallower pathways in a polystyrene microsphere suspension (on average), as already shown previously for circularly polarized light 23 . The orthogonalized and preserved (arc-like) pathways are schematized in Fig.…”
Section: Theoretical and Experimental Spatial Analysis Of Polarimetri...supporting
confidence: 70%
“…The simulation parameters were configured to match the phantom experiment: 108 polarized photon packets (λ=635 nm) were launched into a 2.2×2.2×2.2 cm medium of monodispersed 1.04 μm spheres, each with a refractive index of 1.59, suspended in a host refractive index of 1.33. Remaining details and description of the experimentally validated and publicly available Monte Carlo simulation platform 23 , 43 47 can be found in Ref. 48 and Sec.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations